A General Cutoff Level Combined With Personalized Dynamic Change of Serum Carcinoembryonic Antigen Can Suggest Timely Use of FDG PET for Early Detection of Recurrent Colorectal Cancer. (October 2015) - Huang, Yu-Yi; Lee, Pei-Ing; Liu, Mei-Ching; Chen, Chien-Chih; Huang, Kuo-Cheng; Huang, Andrew T.
<x xml:space="preserve">Abstract</x> Purpose FDG PET that has been used is good for diagnosing asymptomatic colorectal cancer (CRC) recurrence in patients with elevated serum carcinoembryonic antigen (CEA) level. However, there is no reference level of CEA rise that would universally suggest the necessity of a PET study. The purpose of this retrospective study was to identify the high-risk group of CRC recurrence through an examination of the dynamics of the CEA level rise as a recurrence indicator. Patients and Methods Between July 2002 and May 2010, 112 patients (59 men, 53 women; age, 18–87 years) had FDG PET for suspicious CRC recurrence indicated by elevated CEA level. We reviewed the PET results and the medical records for recurrence verification and calculated the ratio of increase and the velocity of change in CEA levels for risk stratification. Results The patient-based sensitivity, specificity, and accuracy of PET are 96.6%, 91.3%, and 95.5%, respectively. The probability of recurrence positively correlated with the CEA level rise and the newly diagnosed disease stage. Carcinoembryonic antigen level greater than 13 ng/mL indicated significantly higher risks of recurrence. In patients with CEA level rise of 13 ng/mL or less, an increase over 3.34 times the individualized baseline also indicated high risks of recurrence. Conclusions A posttreatment CEA level rise to greater than 13 ng/mL is suggestive of the optimal use of FDG PET, and so is a mild increase below 13 ng/mL at an increase rate over 3.34.